2017
DOI: 10.21273/hortsci12026-17
|View full text |Cite
|
Sign up to set email alerts
|

Increased Electrical Conductivity in Nutrient Solution Management Enhances Dietary and Organoleptic Qualities in Soilless Culture Tomato

Abstract: Greenhouse tomato production is shifting to meet emerging consumer needs. Increasing environmental concerns have pressured growers to supply high-quality vegetables using sustainable production methods. The utilization of adapting fertigation to production conditions and/or nutrient solutions of moderately high conductivity seems promising in providing high yields of superior quality while limiting the emission of nutrients to the environment in greenhouse tomato crops. A tomato crop was grown in soill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 35 publications
(62 reference statements)
9
33
2
3
Order By: Relevance
“…found that lycopene content remained unaffected in tomato fruit subjected to saline conditions, whereas Moya et al . reported opposite trends . These contradictory results could be attributed to the severity of salinity stress, since different NaCl levels were applied in those studies, and mild stress (4.5 dS m −1 ) seems to be beneficial to lycopene content of tomato fruit compared to more severe stress (6.0 dS m −1 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…found that lycopene content remained unaffected in tomato fruit subjected to saline conditions, whereas Moya et al . reported opposite trends . These contradictory results could be attributed to the severity of salinity stress, since different NaCl levels were applied in those studies, and mild stress (4.5 dS m −1 ) seems to be beneficial to lycopene content of tomato fruit compared to more severe stress (6.0 dS m −1 ).…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, salinity resulted in an increased level of TSS in tomato fruit prior to storage. The beneficial effects of salinity on the soluble solids content are in agreement with the reports of other investigators, although it is mentioned that such an increase could be the result of a concentration effect when results are expressed on a fresh weight basis rather than the actual increase of TSS …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings showed that SSC increased with increasing salinity levels in both years and for all lines. It has previously been reported that 86 mM NaCl increased SSC content [40]. This result is in also accordance with a previous study [41].…”
Section: Discussionsupporting
confidence: 93%
“…The drainage parameters of the resulting pH, EC, and percentage of volume of fertigation and drainage are commonly used in the practical control of soilless culture (Gorbe and Calatayud, 2010;Moya et al, 2017;Rodríguez et al, 2015;Urrestarazu et al, 2008). Figure 1 shows a graph of the pH and EC values as a function of the acid dose added to a standard nutrient solution with 2.0 mM bicarbonate from the irrigation water.…”
Section: Resultsmentioning
confidence: 99%